PENDEKATAN SOSIOLOGI SASTRA DALAM MENGKAJI KONFLIK DAN RESOLUSI PADA NASKAH DRAMA ‘JERIT MALAM DI KAMPUNG KALONG’ - Ahnaf Fa’iz Djohar; Wahyu Wibowo; Sukirno Sukirno (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
The research entitled "Literary Sociology Approach in Examining Conflict and Resolution in the Drama Script 'Jerit Malam di Kampung Kalong'" aims to find out the causes of conflict and how effective conflict resolution is to overcome the conflict that occurs in the drama script. This research uses qualitative methods to describe the problems and research focus. Qualitative methods are research steps to obtain descriptive data in the form of words from the drama script being studied. The results found that there were 2 factors causing conflict in the drama script and there were 3 effective methods for resolving conflict according to the author. The author hopes that with this research all conflicts that occur in society can be resolved peacefully without violence.